ANALISIS SOSIAL EKONOMI PENGOLAHAN LIMBAH KOTORAN SAPI PERAH DI KECAMATAN KANIGORO KABUPATEN BLITAR - Dzun Nuraini Aziz; Agustina Widyasworo; Nita Opi Ari Kustanti (Universitas Islam Balitar, 2019)
This research is motivated by livestock business activities which not only produce output in the form of tillers, meat or milk, but also cause side output in the form of livestock waste such as feces, urine, feed residue, and water from the cleaning of the cage. Untreated livestock waste can cause environmental pollution. For this reason, a social economic analysis of livestock waste treatment is needed. This research was conducted in May to July 2019 with the location of data collection in Kanigoro District, Blitar Regency. The method used is a qualitative approach with data collection techniques through interviews, observation and documentation. This research uses descriptive analysis with primary and secondary data sources. The results of this study indicate that socially and economically processing livestock manure waste has a positive impact on farmers. A good relationship between farmers and surrounding communities in the cooperation of waste utilization is created by the implementation of waste treatment. Economically, farmers benefit from increased income or saving expenses. It is hoped that this research can encourage farmers to apply livestock waste treatment evenly and sustainably.